Влияние предварительного пластического деформирования на шероховатость поверхности титанового сплава Ti–Si после алмазной доводки - Розенберг, О.А.; Сохань, С.В.; Кузьменко, Н.Н.; Ефросинин, Д.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
Research technique and results are represented for a study of surface roughness and structure at diamond lapping of titanic alloy with system Ti–Si. Because of structure heterogeneity it is impossible to receive stable surface quality after diamond processing on textolite lap. Preliminary surface plastic deforming is added to decrease surface roughness of titanic alloy.